Aspergilloma of maxilla in an immunocompromised patient: A multidisciplinary approach - Deepthi Shetty; Tejaswini Manjunath; Venkatesh Anehosur; Niranjan Kumar (Gülhane Tıp Dergisi, 2025)
Aspergillosis is a rare, invasive, rapidly progressive, and life-threatening fungal disease of the maxillofacial region and what makes the disease sinister is its indolent course and ability to cause death (16%). Early diagnosis and treatment are essential for such infections. We here report a case of an elderly male patient with diabetes mellitus, cardiac disease, and kidney failure who was diagnosed with aspergilloma with osteomyelitis of the right maxilla. Treatment was based on the comorbidities and the clinical, radiological, and histological features of the lesion.